Efficacy of tetravalent dengue vaccine: A systematic review and meta-analysis - Ashish Wasudeo Khobragade; Dilip D Kadam (Indian Journal of Community Medicine, 2021)
Dengue is one of the neglected tropical diseases caused by flavivirus. Live-attenuated tetravalent vaccine is launched for the age group of 9–45 years. It is given in three doses schedule. Eleven studies were included in meta-analysis by following PRISMA guidelines. Healthy persons in the age group of 2–45 years were included in these studies. Statistical analysis was done by “R” software. Pooled relative risk among vaccinated versus control group was calculated using random-effect model. Pooled dengue vaccine efficacy was calculated from relative risk. Heterogeneity and publication bias were assessed using Baujat and funnel plot, respectively. Adverse effects following immunization were reviewed. Pooled vaccine efficacy is 58% (95% confidence interval 46%-67%). I2 statistics is 81.4%.